Application of SWAT model to assess reservoir sedimentation in Song Hinh Hydropower Project, Vietnam - Truong Hoai The Tuyen; Clemente, Roberto S.; Babel, Mukand Singh; Gupta, Ashim Das; Tawatchai Tingsanchali; Electricity of Vietnam (EVN); AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Song Hinh hydropower project has 747.74 km2 of drainage area and was built in 1990s for electricity generation, inigation, and aquaculture purposes. Its infrastructures includes accessed roads and resettlement areas which led to rapid deforestation due to pressure on cultivated land and food production systems. In addition to high rainfall and deforestation, poor management practices with traditional methods might cause increasing soil erosion and decreasing water quality. As a consequence, reservoir sedimentation might threaten the capacity of a 357 million m3 reservoir and electricity production in long term. Soil and Water Assessment Tool (SWAT) model was applied to simulate and estimate the soil erosion and sedimentation of the reservoir which directly affect Song Hinh hydropower project. Input data was collected from many related agencies. Topography maps were collected with 1:50,000 map scale and 40-meter interval contour. Digital Elevation Model (DEM) with resolution of 100-meters was converted using ArcView-GIS. Weather data were obtained from South Central Hydrometeorology Center and Power Engineering Consulting Company 1 (PECC1). Missing rainfall was processed by using linear regression with multiple variables analysis method. Land cover maps, soil maps and its properties were available from Institute of Central Agriculture Planning and Designing (ICAPD) and converted to grid used Arcview-GIS corresponding to DEM's resolution. Base flow was separated by using Base Flow Filter program. The model was run using basic data on land cover in 1993 and 2000. Calibrations was done with stream flow from 1981 to 1988. In this process, Nash-Sutcliffe efficiency was found to be 0.91, 0.9, and 0.72 for annual, monthly, and daily basis respectively. Coefficient of determination are 0.86, 0.92, and 0.74 for annual, monthly, and daily basis respectively. Water balance was checked based on annual values. Measured stream flow data in 1989-1991 was used for verification which had Nash-Sutcliffe efficiency and coefficient of determination of 0.59 and 0.59 respectively. Observed sediment in 1988 was used for sediment transport calibration. It was found that the average annual sedimentation in Song Hinh reservoir is about 830,000 metric tons which is much higher than the estimated value of 343,000 T/year from IWARP. It was also found from sensitivity analysis that soil physical properties and land use had high to very high influence on sediment yield. Four scenarios of conservation practices were evaluated to manage sedimentation of Song Hinh reservoir in long term. It was found that terracing combined with strip cropping is the best management practice (BMP) that can be adopted for controlling sedimentation in the basin.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2007
Keywords: Reservoir sedimentation -- Evaluation -- Vietnam -- Song Hinh Hydropower Project